Effect of Cooperative participation on profitability of fresh fish business in Ogun State Nigeria - Tawakalitu Obasan; Adewunmi Idowu; Adewunmi Sofoluwe; Oluwakayode Oluwasanya; Adebisi Awolumate (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
The study examined the effect of cooperative participation on profitability of fresh fish business in Ogun State Nigeria. A total of one hundred and forty four (144) respondents were selected based on multi-stage sampling technique and were interviewed through well-structured questionnaire. Descriptive statistics such as frequency tables, means, percentages and regression analysis were used to analyse the data collected.The result showed that majority (89.6%) of fresh fish business owners were males;(65.8%) married with a mean age of 50years. The majority (92.4%) of them were educated and had an average household size of 5 persons. The cost and returns analysis revealed that the variable cost accounted for the largest proportion (76%) and (75%) of the total cost of production for the cooperative fish farmers and non cooperative fish farmers respectively. The Profitability index and Rate of return on investment (RRI) were computed as 0.51 and 1.06 respectively. The study concludes that the variables that determine the profitability level of fish business are the size of ponds, cooperative loan, and fish business experience of the farmers and recommends among others that fish farmers should increase their pond size to increase their profit levels